Defining growth requirements of microgreens in space cultivation via biomass production, morpho-anatomical and nutritional traits analysis - Amitrano, Chiara; Paglialunga, Gabriele; Battistelli, Alberto; De Micco, Veronica; Del Bianco, Marta; Liuzzi, Greta; Moscatello, Stefano; Paradiso, Roberta; Proietti, Simona; Rouphael, Youssef; De Pascale, Stefania (Frontiers in Plant Science, 2023)
During long-term manned missions to the Moon or Mars, the integration of astronauts’ diet with fresh food rich in functional compounds, like microgreens, could strengthen their physiological defenses against the oxidative stress induced by the exposure to space factors. Therefore, the development of targeted cultivation practices for microgreens in space is mandatory, since the cultivation in small, closed facilities may alter plant anatomy, physiology, and resource utilization with species-specific responses. Here, the combined effect of two vapor pressure deficit levels (VPD: 0.14 and 1.71 kPa) and two light intensities (150 and 300 µmol photons m−2 s−1 PPFD) on two species for microgreen production (Brassica oleracea var. capitata f. sabauda ‘Vertus’ and Raphanus raphanistrum subsp. sativus ‘Saxa’), was tested on biomass production per square meter, morpho-anatomical development, nutritional and nutraceutical properties. Microgreens were grown in fully controlled conditions under air temperature of 18/24°C, on coconut fiber mats, RGB light spectrum and 12 h photoperiod, till they reached the stage of first true leaves. At this stage microgreens were samples, for growth and morpho-anatomical analyses, and to investigate the biochemical composition in terms of ascorbic acid, phenols, anthocyanin, carotenoids, carbohydrates, as well as of anti-nutritional compounds, such as nitrate, sulfate, and phosphate. Major differences in growth were mostly driven by the species with ‘Saxa’ always presenting the highest fresh and dry weight as well as the highest elongation; however light intensity and VPDs influenced the anatomical development of microgreens, and the accumulation of ascorbic acid, carbohydrates, nitrate, and phosphate. Both ‘Saxa’ and ‘Vertus’ at low VPD (LV) and 150 PPFD increased the tissue thickness and synthetized high β-carotene and photosynthetic pigments. Moreover, ‘Vertus’ LV 150, produced the highest content of ascorbate, fundamental for nutritional properties in space environment. The differences among the treatments and their interaction suggested a relevant difference in resource use efficiency. In the light of the above, microgreens can be considered suitable for cultivation in limited-volume growth modules directly onboard, provided that all the environmental factors are combined and modulated according to the species requirements to enhance their growth and biomass production, and to achieve specific nutritional traits.